2018
DOI: 10.1128/aac.01505-17
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Piperazine-Based Drug Lead for Cryptosporidiosis from the Medicines for Malaria Venture Open-Access Malaria Box

Abstract: Cryptosporidiosis causes life-threatening diarrhea in children under the age of 5 years and prolonged diarrhea in immunodeficient people, especially AIDS patients. The standard of care, nitazoxanide, is modestly effective in children and ineffective in immunocompromised individuals. In addition to the need for new drugs, better knowledge of drug properties that drive in vivo efficacy is needed to facilitate drug development. We report the identification of a piperazine-based lead compound for Cryptosporidium d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(98 citation statements)
references
References 38 publications
6
92
0
Order By: Relevance
“…Consistent with this hypothesis, C. parvum time-kill curve assays showed that the approved drug nitazoxanide, which is effective in immunocompetent adults but equivalent to a placebo in AIDS patients, is likely parasitistatic or very slow acting ( Fig. 3a) 19 . Time-kill curve data were referenced to the vehicle control for each time point in order to isolate the effect of compounds from the spontaneous decline in C. parvum numbers that occurs after 24 to 48 h of in vitro culture.…”
Section: Resultsmentioning
confidence: 58%
See 4 more Smart Citations
“…Consistent with this hypothesis, C. parvum time-kill curve assays showed that the approved drug nitazoxanide, which is effective in immunocompetent adults but equivalent to a placebo in AIDS patients, is likely parasitistatic or very slow acting ( Fig. 3a) 19 . Time-kill curve data were referenced to the vehicle control for each time point in order to isolate the effect of compounds from the spontaneous decline in C. parvum numbers that occurs after 24 to 48 h of in vitro culture.…”
Section: Resultsmentioning
confidence: 58%
“…Efficacy in acute and established murine cryptosporidiosis. AN7973 efficacy was first tested in vivo using a NOD scid IL2rg null (NOD scid gamma (NSG)) mouse model, which is a model of established C. parvum infection 19 . Treatment was begun 7 days after infecting mice by oral gavage with the C. parvum Bunch Grass Farms Iowa isolate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations